علم القراءات وتطور تعليمه في نيجيريا : دراسة تاريخية ميدانية - حمزة، رفاعي أوبا (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research presents a comprehensive historical and field study on the science of the ten readings of the Qur'an and its relation to Nigeria. It begins with the definition of this science, showing the differences between it and similar terms. It examines the origin of the readings of the Quran (Qiraat) and the stages of the development of its existence, the history of its ten readers and their narrators in a comprehensive statement of the bases and origins of each reader, The study also concerns the spread of every reading type in the contemporary Islamic world, the history of the method of gathering readings at one time and the doctrines of the concerned scholars. The research provides a study on the geography of Nigeria and its social, religious and political conditions, and the entry and spread of Islam, and areas inhabited by the majority and minority Muslims in their jurisdictions. It examines the history of the traditional Qur'anic schools and their teaching system. It discusses the systems of the readings of the Quran (Qiraat) in secondary schools, institutes, colleges and universities, and how they spread in Nigeria. The research includes a study on the audiotapes of Nigerian reciters. It also mentions some of the famous reciters of the Muslim world who were influenced by the Nigerians. It reviews the national and international conferences related to the Holy Quran and its recitations in Nigeria, and discusses the establishment of Quranic competitions in the Islamic world, and in Nigeria, and talks about the national and international Quranic competitions and their developments in the world and in Nigeria, it brings their branches and awards, mentioning the names of the most prominent Nigerian winners. The study also mentions contributions of the Nigerian government at all levels to the development of the science of the reading of Quran (Qiraat), reviewing the history of educational missions to the Arab States for the rehabilitation of Nigerian students in that respect, and the general assessment of the contributions of Nigerian scholars in the subject matter. The historical and field reearch methodologies were used through out the research. It concludes with the research findings which include the discovery of Nigerian publications in the field of Qiraat, and that, the teaching of this knowledge has covered all academic levels in Nigeria, while the modern information technology methods, like the internet and Quran online are absent in the field of teaching Quran recitation in Nigeria. The more important suggestions are, to create good coordination among academic syllabuses at various stages in Nigerian institutions that should contain morality lessons as the major target of the Holy Quran teaching. There is a need to establish national Islamic endowment under leadership of Sultan of Sokoto to take care of Quranic projects as well as the establishment of Quranic schools and supporting Quranic traditional institutions.